FEE AUDIT SEBAGAI PEMODERASI PENGARUH AUDITOR SWITCHING PADA KUALITAS AUDIT - Ciptana Putri, Kadek Dwiyani; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 16 No 3 (2016), 2016)
The purpose of this study was to determine the effect of auditor switching on the quality of the audit with the audit fee as moderation. The data used in this study was obtained from BEI is a manufacturing company that publishes the complete audited financial statements ( in rupiah ) listed on the Stock Exchange from 2009-2014. The samples used 168 observations determined by purposive sampling technique. The data analysis technique used is logistic regression and interaction test . The analysis showed that the auditor switching positive effect on audit quality audit. Fee moderate the effect of auditor switching on audit qualit y .
Keywords: auditor switching, audit quality, fee audit